Men Don’t Cry, Women Do? A Myth Exploration of the Archetypes of Contemporary American Novel Grieving Characters - Anam, Zuhrul; Darmawan, Ruly Indra (TEKNOSASTIK, 2024)
The examination of grieving archetypes in contemporary American novels is crucial for understanding the cultural myths surrounding emotional expression, particularly the stereotype that "men don't cry, women do." This study addresses the gap in literature regarding the portrayal of gendered grief by analysing Alice Sebold's "The Lovely Bones." This research uses a descriptive analysis method and semiotic approach to investigate how characters' grieving processes reflect and challenge traditional gender norms. The findings indicate that male and female characters exhibit intuitive, instrumental, and blended grief patterns, thus subverting the conventional stereotypes. This study concludes that literary depictions of grief contribute to the broader cultural narrative and influence perceptions of gendered emotional expression, highlighting the need for a more nuanced understanding beyond simplistic stereotypes.